A Yankee in de Valera's Ireland : a memoir of David Gray - Gray, David, 1870-1968 (Royal Irish Academy, 2012)
Lawyer, soldier, journalist and playwright, David Gray cuts an unlikely diplomatic figure. Born in Buffalo, New York in 1870, he took up the post of US Minister to Ireland in 1940. His memoir of that year is published here.